CORRELATION BETWEEN ABILITY TO RECOGNIZE SENTENCE ERRORS AND ABILITY TO PRODUCE GRAMMATICALLY CORRECT UTTERANCES - Masrizal Masrizal (Universitas Islam Negeri Banda Aceh, 2017)
This article summarizes and reports an empirical study investigating students’ ability in recognizing grammatical errors and producing grammatically correct sentences. Thirty eight university students were involved in a set of grammar tasks which were specifically created to measure their ability to both identify errors and avoid them in language productions. The main purpose of the study is to prove whether their ability to pinpoint errors within sentences resembles their ability in producing grammatically correct sentences using the same features. The study also measures the appropriateness of the test items in order to see how it affects students’ performance. Final test data collected from the students in two different groups reveal that their ability to recognize sentence errors has positive correlation to their ability to produce correct sentences. The correlation figure among the more proficient students (group 2) is relatively larger, indicating that the amount of knowledge on relevant features positively influences, to a certain extent, the quality of language production and responses.